The Effect of Humidity on Microwave Characteristics of Screen Printed Paper‐Based Electronics. Issue 11 (16th April 2018) - Shenton, Samantha A.; Cooke, Michael D.; Racz, Zoltan; Balocco, Claudio; Wood, David
Abstract : This paper addresses one of the key issues in using paper electronics at microwave frequencies. As paper is hygroscopic, the varying moisture content can lead to differing dielectric and even conductive properties of paper electronics and must be taken into consideration in any device design. In this work, coplanar waveguides (CPWs) have been screen printed using silver ink on matt paper. Increasing the relative humidity between 40 and 90% is shown to increase the losses, decrease the propagation velocity and decrease the characteristic impedance of CPWs. The effect of water on both silver flake ink and the matt paper used in this work are considered, and it is shown that the change in permittivity of the substrate as a result of absorbed water within paper is the most dominant factor on the microwave characteristics. The reported findings should be considered in paper‐based applications at microwave frequencies, as the changes in transmission‐line parameters can lead to drastic variations in device and system operation. Abstract : The hygroscopic nature of paper requires the investigation of the impact of humidity on paper‐based electronics at microwave frequencies. Losses, propagation velocity and characteristic impedance of screen‐printed coplanar waveguides are determined between 300 kHz and 3 GHz as a function of relative humidity. A model was developed to calculate the change in dielectric constant with relative humidity.